DEVELOPING THE CRITICO SUPERADORA METHODOLOGY IN A DISSIMILAR REALITY (Fiep Bulletin - online, 2015)
This work has as objective, socialize the experiences with a fourth grade class, fo fundamental teaching, from Margarida Alves school, located on Assentamento Jose Dias, in Inacio Martins City, Paraná. We search to work the physical education with the critico superadora methodology (which have as reference the historical-critical pedagogy), so from the watches realized in the investigated field, was possible analyze that this theory was the most adequate to the dialect thinking of that reality.
Keywords: physical education; methodology; MST